ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PROBABILITAS KEBANGKRUTAN EMPAT BANK DALAM KELOMPOK LG 45 DI BURSA EFEK INDONESIA - Sekargita Agus; Abdul Kohar Irwanto; Tubagus Nur Ahmad Maulana (Pusbindiklat - LIPI, 2014)
Bank is an entity that acts as a financial intermediary that puts the public funds entrusted to it, to be dis- tributed back to the community in form of loans, and the business world at large in form of credit. Outstanding funds through banks can be optimized to support the investment, which in turn encourages economic growth, and improves standards of living and equitable development. Therefore, the banking operations should be monitored closely by the stakeholders. The purpose of this study was to analyze the probability of bankruptcy of the banking sector and to analyze the relationship between accounting information in form of financial ratios (APB, ROA, ROA, ROE, LDR, NPL, ATTM, CAR, and NIM) to the probability of default (PD) by using KMV Merton. The object of this study is banks that are consistent listed in LQ 45 period 2009–2012 and issuing bond. The research result showed that the probability of bank failure from KMV Merton models give an indication of low level of bank failures with the highest rating of AAA, so PT Bank Rakyat Indonesia Tbk., PT Bank Mandiri Tbk, PT Danamon Indonesia Tbk., and PT BPD of West Java and Banten Tbk. are worth to be invested. The regression analysis of financial ratios can explain 88.44% in PD equation model. Based on the regression analysis performed, the independent variables in the regression have a significant effect on the dependent variable of the banks listed in LQ-45, which is the Operating Expenses to Operating Income (ROA) has a positive influence on PD and Against Capital Fixed Assets (ATTM ) has a negative effect on PD.